(untitled) (Research, Society and Development, 2022)
Introduction: In view of the damage that hearing impairment brings to speech perception, it is essential to carry out speech perception assessment in order to improve new technologies and therapeutic strategies. Objective: To establish relationships between hearing ability and performance in speech perception tasks in children with hearing loss. Method: The Speech Intelligibility Index (SII) was established for input signals of 55 and 65 dBSPL of 17 children between five and seventeen years old, with sensorineural hearing loss, hearing aid users, with oral language. They were submitted to the repetition of words with and without meaning in 55 and 65 dBSPL. For analysis, the SII was related to the results obtained in the word lists. Subjects were classified into two groups according to SII 65dB values (>=64% and <64%). Results: Subjects with SII65dB >=64 showed significantly better performance in nonsense and nonsense word recognition tasks. The same tendency was observed in the lists presented at 55 dBSPL. The median of correct answers on the lists showed a significant difference and was considered equivalent. The difference between the groups regarding the consistency of hearing aid use was significant for the SII 55 dB. Conclusion: Other intervening variables in the performance of speech perception tasks should be considered, in the search for the variables that most affect auditory skills. The reduced number of subjects in this study limited the possibility of comparative analysis and the identification of possible frontiers in the SII 65 dB values associated with speech perception skills.